The signal crayfish (Pacifastacus leniusculus) in Lake Tahoe (USA) hosts multiple Aphanomyces species - Makkonen, Jenny; Kokko, Harri; Gökmen, Gökhan; Ward, Judson; Umek, John; Kortet, Raine; Petrusek, Adam; Jussila, Japo (Journal of invertebrate pathology, 2019)
The genus Aphanomyces (Oomycetes) comprises approximately 50 known species of water molds in three lineages. One of the most notorious is Aphanomyces astaci, the causative agent of crayfish plague. In this study, fresh isolates of Aphanomyces were collected from 20 live specimens of the signal crayfish Pacifastacus leniusculus (Dana, 1852) from Lake Tahoe, California, providing 35 axenic cultures of A. astaci as well as two apparently undescribed Aphanomyces spp. isolates. Based on the results of ITS-, chitinase-, mitochondrial rnnS- and rnnL-sequences and microsatellite markers combined, the Lake Tahoe A. astaci isolates were identical to isolates of A. astaci B-haplogroup commonly detected in Europe, and infection experiments confirmed their high virulence towards noble crayfish. One of the two undescribed Aphanomyces spp. isolates was highly similar to an Aphanomyces lineage detected previously in crustacean zooplankton (Daphnia) in Central Europe, while the other was distinct and most closely related (ITS sequence similarity of 93%) to either A. astaci or to Aphanomyces fennicus isolated recently from Astacus astacus in Finland. Neither of the two Aphanomyces spp. isolates caused crayfish mortality under experimental conditions. Our results indicate that the populations of North American signal crayfish can act as carriers of both pathogenic and non-pathogenic Aphanomyces at the same time. Furthermore, considering that a limited number of crayfish individuals from a single location yielded multiple distinct Aphanomyces isolates, our results suggest that substantial species diversity within this genus remains undescribed.
Keywords: Astacoidea; United States; Animals; Virulence; Invasive species; virulence; Crayfish plague; Lakes; Pathogen; zvířata; Spojené státy americké; Parasite; severní raci; jezera; Aphanomyces; Species diversity